3D annotation and manipulation of medical anatomical structures - Vitanovski, Dime; Schaller, Christian; Hahn, Dieter; Daum, Volker; Hornegger, Joachim (Medical Imaging 2009: Biomedical Applications in Molecular, Structural, and Functional Imaging, 2009)
Although the medical scanners are rapidly moving towards a three-dimensional paradigm, the manipulation and annotation/labeling of the acquired data is still performed in a standard 2D environment. Editing and annotation of three-dimensional medical structures is currently a complex task and rather time-consuming, as it is carried out in 2D projections of the original object. A major problem in 2D annotation is the depth ambiguity, which requires 3D landmarks to be identified and localized in at least two of the cutting planes. Operating directly in a three-dimensional space enables the implicit consideration of the full 3D local context, which significantly increases accuracy and speed. A three-dimensional environment is as well more natural optimizing the user's comfort and acceptance. The 3D annotation environment requires the three-dimensional manipulation device and display. By means of two novel and advanced technologies, Wii Nintendo Controller and Philips 3D WoWvx display, we define an appropriate 3D annotation tool and a suitable 3D visualization monitor. We define noncoplanar setting of four Infrared LEDs with a known and exact position, which are tracked by the Wii and from which we compute the pose of the device by applying a standard pose estimation algorithm. The novel 3D renderer developed by Philips uses either the Z-value of a 3D volume, or it computes the depth information out of a 2D image, to provide a real 3D experience without having some special glasses. Within this paper we present a new framework for manipulation and annotation of medical landmarks directly in three-dimensional volume. © 2009 SPIE.

3D Tele-Medical Speech Therapy using Time-of-Flight Technology - Stürmer, Michael; Maier, Andreas; Schaller, Christian; Soutschek, Stefan; Penne, Jochen; Handschu, Rene; Scibor, Mateusz; Nöth, Elmar (4th European Congress for Medical and Biomedical Engineering, 2009)
Tele-medical applications allow the treatment of patients over long distances. This is of special importance in speech therapy, since speech therapists often operate in specialized centers for certain disorders. In this paper we propose a novel therapy system which employs Time-of-Flight (ToF) 3D cameras that acquire 3D surface data in real time. The distance data is compressed within a MPEG stream and transmitted to a remote client where a 3D visualization is implemented. The loss in accuracy compared to the original data is within 1.6 mm and 9.7 mm. The system can be used for real-time streaming.
Keywords: Speech Therapy; Time-of-Flight; Telemedicine; MPEG

A Comparative Error Analysis of Current Time-of-Flight Sensors - Fürsattel, Peter; Placht, Simon; Balda, Michael; Schaller, Christian; Hofmann, Hannes; Maier, Andreas; Riess, Christian (IEEE Transactions on Computational Imaging, 2016)

A novel image based verification method for respiratory motion management in radiation therapy - Khamene, Ali; Schaller, Christian; Hornegger, Joachim; Celi, Juan Carlos; Ofstad, Barbara; Rietzel, Eike; Li, X. Allen; Tai, An; Bayouth, John (2007 IEEE 11th International Conference on Computer Vision, ICCV, 2007)
Precise localization of moving targets is essential to increase local control of the cancer via dose escalation while reducing the severity of normal tissue complication. Localization of targets in real time with radio-opaque marker is less favorable considering the excess radiation dose to the patient and potential complications of implantation. Various external surrogates could provide indications of the targets' positions during the breathing process. However, there is a great deal of uncertainty in the correlation between external surrogates and internal target positions/trajectory during respiratory cycles. In order to address this problem, we have developed an algorithm that automatically establishes correspondences between the fluoroscopic sequence frames taken from the patient on the day of treatment and the various phases of a 4DCT planning data set. Image based mapping/synchronization procedure is performed using an underlying Markov model established for the breathing process. The mapping procedure is formulated as an optimization process and is solved efficiently using a dynamic programming technique. Results on the phantom, synthetic, and real patient data demonstrate the effectiveness of the proposed method in coping with respiratory correlation variations. The approach could primarily be used for automatic gating interval adaptation in the gated radiotherapy. ©2007 IEEE.

Contributions of Time-of-Flight cameras for biomedical applications - Höller, Kurt Emmerich; Schaller, Christian; Tacke, Dominik; Höpfl, Florian; Hornegger, Joachim (Innovationen bei der Erfassung und Analyse bioelektrischer und biomagnetischer Signale, 2008)

Distance error correction for time-of-flight cameras - Fürsattel, Peter; Schaller, Christian; Maier, Andreas; Riess, Christian (Automated Visual Inspection and Machine Vision II, 2017)
Keywords: Time-of-Flight; Systematic Errors; Random Forests

Evaluation of a Time-of-Flight based respiratory motion management system - Ulrich, Christian; Schaller, Christian; Penne, Jochen; Hornegger, Joachim (Bildverarbeitung für die Medizin, 2010)

Image Based Time Series Synchronization for Periodically Moving Targets - Schaller, Christian; Khamene, Ali; Hornegger, Joachim (3rd Russian-Bavarian Conference on Biomedical Engineering, 2007)

Improvement and Evaluation of a Time-of-Flight based patient positioning system - Placht, Simon; Schaller, Christian; Balda, Michael; Adelt, André; Ulrich, Christian; Hornegger, Joachim (Bildverarbeitung für die Medizin, 2010)

Inverse C-arm positioning for interventional procedures using real-time body part detection - Schaller, Christian; Rohkohl, Christopher; Penne, Jochen; Stürmer, Michael; Hornegger, Joachim (Springer-verlag, 2009)
The automation and speedup of interventional therapy and diagnostic workflows is a crucial issue. One way to improve these workflows is to accelerate the image acquisition procedures by fully automating the patient setup. This paper describes a system that performs this task without the use of markers or other prior assumptions. It returns metric coordinates of the 3-D body shape in real-time for inverse positioning. This is achieved by the application of an emerging technology, called Time-of-Flight (ToF) sensor. A ToF sensor is a cost-efficient, off-the-shelf camera which provides more than 40,000 3-D points in real-time. The first contribution of this paper is the incorporation of this novel imaging technology (ToF) in interventional imaging. The second contribution is the ability of a C-arm system to position itself with respect to the patient prior to the acquisition. We are using the 3-D surface information of the patient to partition the body into anatomical sections. This is achieved by a fast two-stage classification process. The system computes the ISO-center for each detected region. To verify our system we performed several tests on the ISO-center of the head. Firstly, the reproducibility of the head ISO-center computation was evaluated. We achieved an accuracy of (x: 1.73±1.11 mm/y: 1.87±1.31 mm/z: 2.91±2.62 mm). Secondly, a C-arm head scan of a body phantom was setup. Our system automatically aligned the ISO-center of the head with the C-arm ISO-center. Here we achieved an accuracy of ± 1 cm, which is within the accuracy of the patient table control. © 2009 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD5.invers_6

Optical Tracking of Respiratory Motion Using a Time of Flight Camera and its Applicability in Emission Tomography - Schuhmann, Peter; Penne, Jochen; Schaller, Christian; Zeintl, Johannes; Hornegger, Joachim; Kuwert, Torsten (NuklearMedizin 2008, 2008)

Patient positioning using 3-D surface registration - Adelt, André; Schaller, Christian; Penne, Jochen; Hornegger, Joachim (Proceedings of the 4th Russian-Bavarian Conference on Biomedical Engineering, 2008)

Robust Real-Time 3D Respiratory Motion Detection Using Time-of-Flight Cameras - Penne, Jochen; Schaller, Christian; Hornegger, Joachim; Kuwert, Torsten (International Journal of Computer Assisted Radiology and Surgery, 2008)
Purpose: Respiratory motion of the patient during data acquisition causes artifacts in the field of emission or computed tomography. Respiratory gating allows to track and correct these artifacts. Materials and methods: In this paper, we present a system that uses the fairly new and off-the-shelf time-of-flight (ToF) technology to compute a dense estimate of the three-dimensional respiratory motion of a patient. The work is characterized by three key contributions. The first is the employment of ToF sensors. Using ToF sensors, it is feasible to acquire a dense 3D surface model of the chest and abdomen of the patient with more than 15 frames per second. The second contribution is an algorithm to derive a surface representation which enables the estimation of the 3D respiratory motion of the patient, which is sufficient to compute 1D breathing signals for scalable specific regions of interest like chest and abdomen. The proposed data-driven algorithm models the chest and abdomen three-dimensionally by fitting distinct planes to different regions of the torso of the patient. The third contribution is the possibility to derive a sub-millimeter accurate 1D respiratory motion signal by observing the displacement of each plane. Results: Our ToF modeling approach enables marker less, real-time, 3D tracking of patient respiratory motion with an accuracy of 0.1 mm. Conclusion: Thus, our approach provides 1D breathing signals for scalable anatomical regions of interest with sufficient accuracy for artifact reduction in SPECT or X-ray angiography. © CARS 2008.
UnivIS-Import:2017-11-06:Pub.2008.tech.IMMD.IMMD5.robust_2

Robust Real-Time 3D Time-of-Flight Based Gesture Navigation - Penne, Jochen; Soutschek, Stefan; Schaller, Christian; Hornegger, Joachim (Workshop Proceedings der Tagungen Mensch&Computer 2008, DeLFI 2008 und Cognitive Design 2008, 2008)

ROCHADE: Robust Checkerboard Advanced Detection for Camera Calibration - Placht, Simon; Fürsattel, Peter; Assoumou Mengue, Etienne; Hofmann, Hannes; Schaller, Christian; Balda, Michael; Angelopoulou, Elli (Lecture Notes in Computer Science, 2014)
We present a new checkerboard detection algorithm which is able to detect checkerboards at extreme poses, or checkerboards which are highly distorted due to lens distortion even on low-resolution images. On the detected pattern we apply a surface fitting based subpixel refinement specifically tailored for checkerboard X-junctions. Finally, we investigate how the accuracy of a checkerboard detector affects the overall calibration result in multi-camera setups. The proposed method is evaluated on real images captured with different camera models to show its wide applicability. Quantitative comparisons to OpenCV's checkerboard detector show that the proposed method detects up to 80% more checkerboards and detects corner points more accurately, even under strong perspective distortion as often present in wide baseline stereo setups. © 2014 Springer International Publishing.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.rochad
Keywords: Checkerboard Detection; Lens Distortion; Low Resolution Sensors; Multi Camera Calibration; Saddle-Based Subpixel Refinement

Surface-based Respiratory Motion Classification and Verification - Müller, Kerstin; Schaller, Christian; Penne, Jochen; Hornegger, Joachim (Bildverarbeitung für die Medizin 2009, 2009)

Time-of-Flight sensor for patient positioning - Schaller, Christian; Adelt, Andre; Penne, Jochen; Hornegger, Joachim (Medical Imaging 2009: Biomedical Applications in Molecular, Structural, and Functional Imaging, 2009)
In this paper we present a system that uses Time-of-Flight (ToF) technology to correct the position of a patient in respect to a previously acquired reference surface. A ToF sensor enables the acquisition of a 3-D surface model containing more than 25,000 points using a single sensor in real time. One advantage of this technology is that the high lateral resolution makes it possible to accurately compute translation and rotation of the patient in respect to a reference surface. We are using an Iterative Closest Point (ICP) algorithm to determine the 6 degrees of freedom (DOF) vector. Current results show that for rigid phantoms it is possible to obtain an accuracy of 2.88 mm and 0.28? respectively. Tests with human persons validate the robustness and stability of the proposed system. We achieve a mean registration error of 3.38 mm for human test persons. Potential applications for this system can be found within radiotherapy or multimodal image acquisition with different devices. © 2009 SPIE.

Time-of-flight sensor for respiratory motion gating - Schaller, Christian; Penne, Jochen; Hornegger, Joachim (Medical Physics, 2008)
In this technical note we present a system that uses time-of-flight (ToF) technology to acquire a real-time multidimensional respiratory signal from a 3D surface reconstruction of the patient's chest and abdomen without the use of markers. Using ToF sensors it is feasible to acquire a 3D model in real time with a single sensor. An advantage of ToF sensors is that their high lateral resolution makes it possible to define multiple regions of interest to compute an anatomy-adaptive multi-dimensional respiratory signal. We evaluated the new approach by comparing a ToF based respiratory signal with the signal acquired by a commercially available external respiratory gating system and achieved an average correlation coefficient of 0.88. © 2008 American Association of Physicists in Medicine.

Touchscreen ohne Touch - Berührungslose 3D Gesten-Interaktion für den Operationssaal (Touchscreen without Touch - Touchless 3D Gesture Interaction for the Operation Room) - Penne, Jochen; Soutschek, Stefan; Stürmer, Michael; Schaller, Christian; Placht, Simon; Kornhuber, Johannes; Hornegger, Joachim (i-com : Zeitschrift für interaktive und kooperative Medien, 2009)